Tingkat Depresi, Kecemasan dan Stres Pasien Gagal Ginjal Kronik yang Menjalani Hemodialisa - Ivanna Femi Baransano; Evelyn Hemme Tambunan (NHM PRESS, 2023)
Chronic renal failure is a chronic and irreversible impairment of kidney function that requires lifelong hemodialysis therapy. This condition causes chronic renal failure patients to experience depression, anxiety and stress. This study was conducted to determine the level of depression, anxiety and stress of chronic renal failure patients undergoing hemodialysis therapy. This study is non-experimental using a quantitative descriptive design with a cross sectional approach. The population in this study amounted to 70 people, and the determination of the sample using convenience sampling technique was as many as 57 subjects. Data collection using the Indonesian version of the Depression Anxiety Stress Scale-42 (DDAS-42) questionnaire which has been valid and reliable, consisting of 42 question items to measure the level of depression (14 items), anxiety (14 items) and stress (14 items). Data analysis in this study used a univariate test. The results showed that the depression level of chronic renal failure patients undergoing hemodialysis is almost entirely (91%) in the normal depression category, some (56.1%) are at normal anxiety levels, almost entirely (91%) are at normal stress levels and a small proportion (9%) are in the mild stress category. The description of the level of depression, anxiety and stress of chronic renal failure patients undergoing hemodialysis is in the normal and mild categories. Further research can be done by exploring more deeply the factors associated with the level of depression, anxiety and stress of chronic renal failure patients undergoing hemodialysis.